The relationship between adult literacy programme and practical skill of learners (2022)
The human capital resources of a country can function only within the limit of their literacy level. Illiteracy has been recognised as a world problem that hamper development projects especially in developing countries of Africa of which Nigeria is a part. The goal of this programme was to ensure that participants acquired literacy and numeracy skills. The nation-wide campaigns did not yield many results, especially in the rural areas because there were fewer adult education centres, coupled with inadequate staff and funds. The purpose of this study was to investigate the relationship between adult literacy programme and practical skills of leaners. The study adopted descriptive survey design of Ex-post facto type. Simple random sampling will be used to select 20 of the instructors and 100 adult learners out of the total population from the department of adult Education. University of Ibadan. The sample size will therefore be 120. The research instrument for this study will be a structured questionnaire made up of 20 items. The result revealed that there was significant relationship between adult literacy programmes and adult learners practical skills (r = -0.253, n= 120, P < .05). The Null hypothesis is rejected. The adult literacy programmes had significant influence or leaners’ practical skills